Cognitive Attentional Syndrome and Metacognitive Beliefs in Male Sexual Dysfunction: An Exploratory Study. (May 2017) - Giuri, Simona; Caselli, Gabriele; Manfredi, Chiara; Rebecchi, Daniela; Granata, Antonio; Ruggiero, Giovanni Maria; Veronese, Guido
Erectile dysfunction (ED) and premature ejaculation (PE) are two forms of male sexual disorder with both psychological and physical features. While their cognitive, attentional, and affective components have been investigated separately, there is a lack of knowledge about the role played by cognitive attentional syndrome in their onset and maintenance. The aim of the present study was to investigate the possible contribution of perseverative thinking styles and thought control strategies to the development and maintenance of ED and PE. The authors hypothesized that such modes of processing might constitute a cognitive attentional syndrome specific to these disorders and sustained by particular metacognitive beliefs. A semistructured interview was administered to 11 participants with ED and 10 with PE in order to assess their metacognitive beliefs and cognitive attentional processes. The results suggest that individuals with ED and PE adopt a range of cognitive attentional strategies aimed at improving their sexual performance, and endorse both positive and negative metacognitive beliefs about these thinking responses. Overall, their cognitive and attentional patterns worsened negative internal states, reduced sexual excitement, detached them from their bodily sensations, and hindered sexual functioning. These preliminary findings suggest that perseverative thinking, thought control strategies, and metacognitive beliefs may play a key role in the onset and maintenance of male sexual dysfunction.